Determining intracellular lipid content of different oleaginous yeasts by one simple and accurate Nile Red fluorescent method. Issue 6 (3rd July 2019) - Zhao, Cheng; Luo, Mu-Tan; Huang, Chao; Chen, Xue-Fang; Xiong, Lian; Li, Hai-Long; Chen, Xin-De
Abstract: A simple and accurate Nile Red fluorescent method was built to evaluate the lipid content of three different oleaginous yeasts by one standard curve. The staining of cells can be observed clearly by laser scanning confocal microscope, showing that Nile Red can enter into the cells of oleaginous yeasts easily. A series of conditions such as pretreating temperature, cell suspension concentration (OD600 ), staining time, Nile Red concentration and the type of suspension solvent were learnt systematically to obtain the optimal process parameters for Nile Red staining. After optimization, the fitting curve of Nile Red fluorescent method was established under suitable conditions (pretreating temperature: 50 °C, OD600 : 1.0; staining time: 5 mins; Nile Red concentration: 1.0 μg/mL; suspension solvent: PBS) and it had a suitable correlation coefficient ( R 2 = 0.95) for lipid content measurement of different oleaginous yeasts. By this study, the possibility of lipid content determination of different oleaginous yeasts by one fitting curve can be proven and this will improve the efficiency of researches related to microbial lipid production.